Critical Thinking and Gender: A Case in College Students - Alifiah Pratiwi; Ray Suryadi; Bintang Permana Listyawati; Susi Astiantih; Syamsinar (Journal of Education and Culture, 2025)
Critical thinking has been a serious problem for college English Education students in Universitas Sembilanbelas November Kolaka as they were required to critically write a research report for their final project. In order to know their critical thinking ability related to gender, this study described critical thinking among male students and female students. For that purpose, 6 college students (3 male and 3 female) of semester VI have been selected to participate this research by answering a Critical Thinking Mindset Self–Rating Form proposed by Facione and Facione (2014, p. 14) which consisted of 20 ‘yes or no’ questions to measure the students’ level of critical thinking. The finding indicated the disposition of college students both male and female toward critical thinking was considerably different.